2013
DOI: 10.3354/esr00464
|View full text |Cite
|
Sign up to set email alerts
|

To ping or not to ping: the use of active acoustic devices in mitigating interactions between small cetaceans and gillnet fisheries

Abstract: Active sound emitters ('pingers') are used in several gillnet fisheries to reduce bycatch of small cetaceans, and/or to reduce depredation by dolphins. Here, we review studies conducted to determine how effective these devices may be as management tools. Significant reductions in bycatch of harbour porpoise Phocoena phocoena, franciscana Pontoporia blainvillei, common Delphinus delphis and striped dolphin Stenella coeruleoalba, and beaked whales as a group have been demonstrated. For harbour porpoise this resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 56 publications
(82 reference statements)
1
134
1
Order By: Relevance
“…It has been noted, for example, that despite observed 90% reductions in bycatch rates of porpoises associated with the use of pingers in scientifically designed trials, longer term efficacy in commercial fisheries can be lower as fishers' enthusiasm for the added workload (such as battery changing) diminishes (Dawson et al 2012). For bycatch mitigation measures to work in practice, rather than in controlled experiments, they must be easy to assimilate into normal fishing practices and effective long term compliance also requires the fishing community to be convinced of their utility (Poonian et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been noted, for example, that despite observed 90% reductions in bycatch rates of porpoises associated with the use of pingers in scientifically designed trials, longer term efficacy in commercial fisheries can be lower as fishers' enthusiasm for the added workload (such as battery changing) diminishes (Dawson et al 2012). For bycatch mitigation measures to work in practice, rather than in controlled experiments, they must be easy to assimilate into normal fishing practices and effective long term compliance also requires the fishing community to be convinced of their utility (Poonian et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed description of each factor and the evidence for correlation with bycatch rates is available as a bibliography in Supplementary Material. (Dawson et al 2012), but this is given no more weight in our table than a single study that has shown that some bird bycatch can be reduced with the use of acoustic deterrents (Melvin et al 1999a). …”
Section: Factors Related To Bycatch Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, using pingers in these areas may cause considerable issues (Franse, 2005). In their review, Dawson et al, (2013) indicated that the permenant use of pingers in adequate habitats may cause displacement of dolphins from their important habitats especially for species which have small home ranges. On the other hand, considering the fact that pinger signals from the entire Danish gillnet fleet could potentially cover <1% of the porpoises' habitat, displacement does not seem to be a trouble.…”
Section: Habitat Exclusionmentioning
confidence: 99%
“…Dawson et al 2013, this Theme Section): (1) controlled experiments in commercial gillnet fisheries (e.g. Bordino et al 2002, Barlow & Cameron 2003; (2) observations of bycatch rates in fisheries in which pingers are used as part of a mitigation strategy (e.g.…”
Section: Introductionmentioning
confidence: 99%